1990
DOI: 10.1007/bf01741720
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antitumor activity in macrophages by mycoplasmas in concert with interferon

Abstract: The in vitro growth of tumor cells infected with mycoplasmas was suppressed by macrophages pretreated with interferon (IFN), but the growth of mycoplasma-free tumor cells was not suppressed. Pretreatment of macrophages with IFN plus mycoplasmas or their soluble factors either simultaneously or sequentially, IFN first and mycoplasmas second, but not in the reverse order, was effective in activating macrophages to suppress the growth of mycoplasma-free tumor cells. Macrophages from C3H/HeJ mice (which respond on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…We documented previously that various species of mycoplasmas were able to activate M0 primed by IFNct to make them antitumor effector cells [18]. In this study, we have shown that chicken mycoplasmas, as well as lipopolysaccharide, activate M0 in concert with IFNy, The M0-activating capacity of mycoplasmas is quite resistant to heat, acid, or trypsin, and relatively labile in alkaline solutions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We documented previously that various species of mycoplasmas were able to activate M0 primed by IFNct to make them antitumor effector cells [18]. In this study, we have shown that chicken mycoplasmas, as well as lipopolysaccharide, activate M0 in concert with IFNy, The M0-activating capacity of mycoplasmas is quite resistant to heat, acid, or trypsin, and relatively labile in alkaline solutions.…”
Section: Discussionmentioning
confidence: 75%
“…We documented in a previous paper that the host resistance to tumors was enhanced in mice receiving different species of mycoplasmas and interferon (IFN) c~ [18]. Our in vitro investigation demonstrated that mycoplasmas, whether tumor-cell-bound or in free form, play a role, as a second signal for macrophages (M0) primed by IFN~ as a first signal, in the activation of M0 to acquire tumoricidal capacity.…”
Section: Introduetionmentioning
confidence: 72%
“…Because Mycoplasma contamination of cell lines can wreak havoc on cellular studies, high-quality laboratories periodically test cultures for this pathogen. Identification of Mycoplasma in cell lines is also of concern to those who perform in vivo studies because of the well-documented effects of contamination on cell growth and the immune system (Uno et al 1990; Ushio et al 1995). Caution is further warranted as the administration of Mycoplasma-contaminated cells to immunocompromised mice (and other strains) can result in sepsis and other clinical illnesses (Dodds et al 2003).…”
Section: Mycoplasmamentioning
confidence: 97%
“…Mycoplasmas activate macrophages by a mechanism different from that used by LPS inasmuch as they act upon macrophages from LPSnonresponsive C3H/HeJ mice (263,299,413,414,443,463). The effects of mycoplasmas were not inhibited by polymyxin B (463,480) and synergized with LPS in triggering TNF-␣ production by macrophages from LPS-responsive mice (413,414). It appears that while mycoplasmas evade phagocytosis, they interact with mononuclear and polymorphonuclear phagocytes and exert either suppressive or stimulating effects upon them by a combined action of direct and indirect cytokine-mediated effects.…”
Section: Activation Of Immune Cells By Mitogenic Mycoplasmasmentioning
confidence: 99%
“…Studies to elucidate the mechanisms by which mycoplasmas trigger macrophage tumoricidal activity have clearly established that the organisms induced the production of TNF-␣ that subsequently played a major role in toxicity toward tumor cells (12,149,413,414). Mycoplasmas activate macrophages by a mechanism different from that used by LPS inasmuch as they act upon macrophages from LPSnonresponsive C3H/HeJ mice (263,299,413,414,443,463). The effects of mycoplasmas were not inhibited by polymyxin B (463,480) and synergized with LPS in triggering TNF-␣ production by macrophages from LPS-responsive mice (413,414).…”
Section: Activation Of Immune Cells By Mitogenic Mycoplasmasmentioning
confidence: 99%